Persepsi Siswa Tentang Pelayanan Tenaga Administrasi Sekolah di SMKN 1 Enam Lingkung - Pungki Cindy Ashari; Hadiyanto Hadiyanto; Nelitawati Nelitawati; Ermita Ermita (Journal of Educational Administration and Leadership, 2021)
This study is based on obtaining an overview of students perceptions of the service of school administrative personnel. The study uses quantitative research methods. As for the population of this study were students of class X and class XI at SMKN 1 Enam Lingkung. This study shows students perceptions about the service of school adminitrative personnel in SMKN 1 Enam Lingkung: a) the friendlinnes aspect with an average score of 4,16, b) the comfort aspect with an average score of 4,13, c) the responsibility aspect with an average score of 4,11, d) the responsiveness aspect with an average score of 4,15, e) the aspect of ease of with service had an average score of 4,20. Be concluded that students perceptions of service of school administrative personnel at SMKN 1 Enam Lingkung with an average score of 4,15. Suggestions that can be given are efforts to maintain and improve the service for school administrative personnel to make it better.